Sustainable planning model toward reviving Lake Urmia - Alipour, Habib; Olya, Hossein Ghasemi Tangal (Routledge Journals, Taylor & Francis Ltd, 2015)
Lake Urmia (Urumieh in Persian) in north-western Iran is one of the largest permanent hyper-saline lakes in the world and the largest lake in the Middle East. It has numerous ecological, economic and social implications in terms of biodiversity, climate, species, habitat, tourism and recreation. However, during the past decade, the lake has shrunk significantly and its depth has fallen by almost 6m. Contrary to other studies that have focused on the geomorphology of the lake, this study analyses the socio-environmental impact and provides a sustainable adaptive governance management model for its revival. This study reveals that unless various stakeholders and affected parties are actively involved in an implementable adaptive governance model, the fate of the lake will remain uncertain.
Keywords: sustainable governance; disappearing lake; natural resources management; adaptive strategy; Lake Urmia; Iran